Comparative study of locally commercialized vermicompost and sago pith waste vermicompost and effects on maize growth - Pulusagi, Elton Tran (2014)
The vermicompost industry in Malaysia has grown rapidly in recent years. However, there is a lack of documentation on the quality of commercially available vermicomposts; moreover, there are no guidelines for the production of quality vermicomposts. This study was carried out to characterise vermicomposts available in Selangor's local market and to determine the optimum formulation of sago pith waste mixture for vermicomposting as one of the method to convert it into valueadded products. Sago pith waste (SPW) is a starchy solid waste produced during the production of sago starch. Due to high production of sago starch in Sarawak, 32,000 tonnes of sago waste ( dry weight basis) is produced annually. Vermicomposting had been proven to be one of the practical methods in agricultural waste management but very little work had been reported so far on vermicomposting of sago waste. In this study, survey had been done to access the quality of the vermicompost available in the market in Selangor by visiting the vermicompost producers and characterizing these vermicompost. From the vermicompost collected, the feedstocks mainly used were spent mushroom substrate (SMS), sawdust (SD), paddy straw (PS) and co-composted with either cow manure (CM), goat manure (GM), and/or horse manure (HM). The N, P and K content of local vermicomposts are at the range of 1.50 - 2.16%, 0.54 - 1.89%, and 0.39 - 1.73% respectively. The humic acid concentrations in the vermicompost were within 16.7 - 24%. From this study, it was observed that the chemical properties of vermicomposts varied according to the type of the initial feedstock, earthworms used and vermicomposting procedure. The nutrient contents of these vermicompost were compiled and were used to compare with SPW vermicompost produced in this study. The nutrient content ranges of these commercially available vermicompost were acceptable according to Australian Standard for compost, AS 4454. Vermicomposting of SPW was conducted co-composted with either CM or GM at ratio 1: 1, l :2, l :3 using Eisenia fetida and harvested at three different vermicomposting durations (20, 45 and 60) in randomized completely block design (RCBD). Eiseniafetida or the tigerworm used in this study were able to break down the fibrous sago pith waste mixture with the animal manure into finer fonn resembling compost. SPW vermicompost produced in this study have higher total N and humic acid content compared to vermicomposts collected from Selangor's local market, at 2.16-3.79% and 19.33 -23.00% while the micronutrient contents such as Zn, Cu, Fe and Mn were at the permitted levels. Therefore, SPW vennicompost produced in this study are better compared to the commercial vermicomposts that were collected from Selangor's local market used in this study. Maize applied with vermicomposts showed healthier growth compared to maize applied with chemical straight fertilizer which is stunted. Vermicomposts used in this study were able to buffer or improve the soil pH from 4.6 to 5.7. Maize applied with SPW vermicompost showed higher uptake for total K, Ca, and Mg compared to chemical straight fertilizer and selected commercial vermicompost. Comparing the SPW vermicomposts on the maize crop perfonnance, SPW2+GM1 and SPW2+CM1 harvested at day 60 showed the better result compare to other mixtures at different harvesting period and should be used for production of SPW vermicompost.